Plastome structure and adaptive evolution of Calanthe s.l. species - Yanqiong Chen; Hui Zhong; Yating Zhu; Yuanzhen Huang; Shasha Wu; Zhongjian Liu; Siren Lan; Junwen Zhai (PeerJ, 2020)
Calanthe s.l. is the most diverse group in the tribe Collabieae (Orchidaceae), which are pantropical in distribution. Illumina sequencing followed by de novo assembly was used in this study, and the plastid genetic information of Calanthe s.l. was used to investigate the adaptive evolution of this taxon. Herein, the complete plastome of five Calanthe s.l. species (Calanthe davidii, Styloglossum lyroglossa, Preptanthe rubens, Cephalantheropsis obcordata, and Phaius tankervilliae) were determined, and the two other published plastome sequences of Calanthe s.l. were added for comparative analyses to examine the evolutionary pattern of the plastome in the alliance. The seven plastomes ranged from 150,181 bp (C. delavayi) to 159,014 bp (C. davidii) in length and were all mapped as circular structures. Except for the three ndh genes (ndhC, ndhF, and ndhK) lost in C. delavayi, the remaining six species contain identical gene orders and numbers (115 gene). Nucleotide diversity was detected across the plastomes, and we screened 14 mutational hotspot regions, including 12 non-coding regions and two gene regions. For the adaptive evolution investigation, three species showed positive selected genes compared with others, C. obcordata (cemA), S. lyroglossa (infA, ycf1 and ycf2) and C. delavayi (nad6 and ndhB). Six genes were under site-specific positive selection in Calanthe s.l., namely, accD, ndhB, ndhD, rpoC2, ycf1, and ycf2, most of which are involved in photosynthesis. These results, including the new plastomes, provide resources for the comparative plastome, breeding, and plastid genetic engineering of orchids and flowering plants.